(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Tuberculous lymphadenopathy is the most common form of extra-pulmonary tuberculosis and poses a significant diagnostic challenge. Early and accurate diagnosis is essential for timely treatment. This study was conducted to compare the diagnostic utility of Cartridge-Based Nucleic Acid Amplification Test (CBNAAT) with Fine Needle Aspiration Cytology (FNAC) and Histopathological Examination (HPE) in suspected palpable tuberculous lymphadenopathy. Methodology: A prospective comparative study was conducted in the Department of Pathology in collaboration with the Department of General Surgery at Sree Mookambika Institute of Medical Sciences, Kulasekharam, from July 2025 to January 2026. Fifty patients with suspected palpable tuberculous lymphadenopathy were enrolled. Following clinical evaluation and baseline investigations, FNAC was performed in all cases. Subsequently, excisional lymph node biopsy was carried out and specimens were subjected to CBNAAT and histopathological examination. Histopathology was considered the reference standard. Statistical analysis was performed using Epi Info software. Results: Histopathology diagnosed tuberculosis in 60% of cases, FNAC in 58%, and CBNAAT detected Mycobacterium tuberculosis in 46% of cases. FNAC demonstrated a sensitivity of 93.1%, specificity of 85.7%, positive predictive value of 90%, and negative predictive value of 90%. CBNAAT showed a sensitivity of 100%, specificity of 74.07%, positive predictive value of 66.66%, and negative predictive value of 100%. Rifampicin resistance was detected in 10% of microbiologically confirmed cases. Conclusion: FNAC is an effective initial diagnostic tool, while CBNAAT provides rapid microbiological confirmation and detection of rifampicin resistance. Combined use of FNAC, CBNAAT, and histopathology improves the diagnostic accuracy of tuberculous lymphadenopathy.